Co-transcriptional DNA and RNA Cleavage during Type III CRISPR-Cas Immunity - Samai, Poulami; Pyenson, Nora; Jiang, Wenyan; Goldberg, Gregory W; Hatoum-Aslan, Asma; Marraffini, Luciano A (Cell, 2015)
Immune systems must recognize and destroy different pathogens that threaten the host. CRISPR-Cas immune systems protect prokaryotes from viral and plasmid infection utilizing small CRISPR RNAs that are complementary to the invader's genome and specify the targets of RNA-guided Cas nucleases. Type III CRISPR-Cas immunity requires target transcription, and whereas genetic studies demonstrated DNA targeting, in vitro data have shown crRNA-guided RNA cleavage. The molecular mechanism behind these disparate activities is not known. Here, we show that transcription across the targets of the Staphylococcus epidermidis type III-A CRISPR-Cas system results in the cleavage of the target DNA and its transcripts, mediated by independent active sites within the Cas10-Csm ribonucleoprotein effector complex. Immunity against plasmids and DNA viruses requires DNA, but not RNA, cleavage activity. Our studies reveal a highly versatile mechanism of CRISPR immunity that can defend microorganisms against diverse DNA and RNA invaders.